Body mass index and association with use of and distance from places for physical activity and active leisure among schoolchildren in Brazil. Cross-sectional study - Rossi, Camila Elizandra; Correa, Elizabeth Nappi; Neves, Janaina das; Gabriel, Cristine Garcia; Benedet, Jucemar; Rech, Cassiano Ricardo; Vasconcelos, Francisco de Assis Guedes de (São Paulo Medical Journal, 2018)
BACKGROUND: We evaluated associations between use of public places for physical activity and active leisure (PAAL) and their distances from subjects’ homes and indicators of overweight and obesity, among schoolchildren from different socioeconomic levels, in the city of Florianópolis, Brazil. DESIGN AND SETTING: Cross-sectional study conducted on a sample of 2,152 schoolchildren aged 7 to 14 years, enrolled at 30 public and private schools. METHODS: The exposure variables were the use of public places for PAAL in the neighborhood and their distance from schoolchildren’s homes. The outcomes were body mass index (BMI) and waist circumference (WC). Univariate and multivariate linear regression analyses were conducted according to income strata. RESULTS: Among the schoolchildren from low-income families, living closer to parks/playgrounds was associated with lower BMI (β = -2.15; 95% confidence interval, CI = -2.53; -1.77) and lower WC (β = -0.11 95% CI = -0.17; -0.05), while living at these distances from football pitches was associated with higher BMI (β = 1.73; 95% CI = 0.31; 3.15) and larger WC measurements (β = 0.03; 95% CI = 0.005; 0.14). Among the schoolchildren in low-income groups, living at an intermediate distance from beaches was associated with lower BMI (β = -1.10; 95% CI = -1.61; -0.59). CONCLUSION: Living closer to parks/playgrounds was associated with lower BMI and WC among school-children from low-income families. Living closer to football pitches was associated with higher BMI and WC among these schoolchildren. Living at intermediate distances from beaches was associated with lower BMI among these schoolchildren.